Numerical Simulation of Helicopter Rotor Performance Degradation in Natural Rain Encounter - Guozhi Li; Yihua Cao (International Journal of Aerospace Engineering)
Sustained flight operation in the rain conditions is still a challenge to a pilot. This problem can be mainly attributed to the aerodynamic performance degradation of aircraft. In this article, in order to quickly understand the influence of rainfall aiming at the engineering application, an approach to predict helicopter rotor performance degradation in heavy rain encounters is presented. Firstly, we develop a computational fluid dynamics- (CFD-) based method of simulation of the blade airfoil under natural rain scenario and different angles of attack in order to obtain a data-driven basis relating to multiple working conditions of the rotating blades for further analysis. Then, these data are studied using a discretization analysis method of rotor aerodynamics. CFD simulations are conducted, including the case of NACA 0012 airfoil with 10 m chord length, and the case of SC1095 airfoil used in a full-scale rotor of UH-60A helicopter. Prediction of helicopter rotor performance degradation is carried out in a thunderstorm heavy rain with the rain rate of 1500 mm/h using this full-scale rotor. The quantitative results indicate that heavy rain dramatically degrades the rotor performance. The maximum percentage decrease in lift coefficient of this full-scale rotor blade airfoil is reached by 12.75%. The maximum percentage increase in drag coefficient of this full-scale rotor blade airfoil is reached by 26.51%. The maximum percentage decrease in averaging lift-to-drag ratio of this full-scale rotor disk is reached by 26.39%.